Genomics: A Very Short Introduction - John Archibald (Oxford Oxford University Press, 2018)
Genomics has transformed the biological sciences. From epidemiology and medicine to evolution and forensics, the ability to determine an organism's complete genetic makeup has changed the way science is done and the questions that can be asked of it. Genomics: A Very Short Introduction explores the science of genomics and its rapidly expanding toolbox. Sequencing a human genome can now take only a few days and those of simple bacteria and viruses, a matter of hours. The resulting sequences can be used to better understand our biology in health and disease and to 'personalize' medicine. This VSI explains the implications for science and society today and in the future.